Ethical challenges in European parliamentary debates with regards to audiovisual sexual risks on the internet - Pastorino, Agnese (Penerbit Universiti Kebangsaan Malaysia, 2020)
Within European political debate on audio-visual sexual risks for children on the Internet, liberal positions on freedom of expression (Article 19, Universal Declaration of Human Rights, 10 Dec. 1948) are balanced by protectionist approaches highlighting the need for child protection (Convention on the Rights of the Child, 1989). Moreover, other political issues are raised with regards to ethical concerns, such as cultural diversity or censorship. Ethical considerations vary among European media systems due to different historical, cultural and political backgrounds. The hypothesis is that these ethical arguments reflect the historical and cultural diversity of the European scenario. Based on this assumption, the piece of research retrieved ethical reflections focused on audio-visual sexual risks on the Internet and the European media policy regarding child protection. A field study has been carried out through the online archive of European Parliament’s plenary. The corpus collected 45 European Parliamentary debates held between 2001 and 2016. Firstly, content analysis has been applied with ATLAS.ti; secondly, a hierarchical descendant classification has been carried out with the Alceste method (IRaMuTeQ). As a result, the defence of protectionist values, such as consumer and child protection, is justified by violence prevention. Moreover, ethical issues are related to product placement and protection of cultural diversity. Four main themes are highlighted; they are the following ones: the equilibrium between public service and commercial interests, child pornography and sexual exploitation of children, the balance between freedom of expression, and child protection, the relation between freedom of expression and censorship.